A comparision of semantic and communicative approaches to translation based on excerpts taken from the book South America by Frank Carpenter. - Cangá Corozo, Ángel David (2018)
This research project consists of a comparison of semantic and communicative approaches to translation, applied to some excerpts taken from the book South America by Frank Carpenter, in order to prove the hypothesis that the communicative renderings would attain better targeted audience acceptance. To determine the features that each approach should fulfill, a specially designed parameter chart was made up, based on some Newmark and Nida’s theories of translation. Subsequently, a linguistic analysis chart was also designed, where each excerpt was rendered according to each approach, and then analyzed according to the parameter chart. In addition, some of those comparative renderings were used to develop a survey in which forty people had to choose the renderings they found more fluent and natural. Finally, the excerpts rendered with the communicative approach were compiled and presented as a whole in the translation of a chapter of the book, combining there a pattern of four different colors that help the reader to identify translation equivalents.